\(x:y=(a+2): (a-2)\)
বা, \(\cfrac{x}{y}=\cfrac{a+2}{a-2}\)
বা, \(\cfrac{x^2}{y^2} =\cfrac{(a+2)^2}{(a-2)^2}\)
[উভয়পক্ষের বর্গ করে পাই ]
বা, \(\cfrac{x^2}{y^2} =\cfrac{a^2+4a+4}{a^2-4a+4}\)
বা, \(\cfrac{x^2+y^2}{x^2-y^2}\)
\(=\cfrac{(a^2+4a+4)+(a^2-4a+4)}{(a^2+4a+4)-(a^2-4a+4)}\)
[যোগভাগ প্রক্রিয়ার সাহায্যে ]
বা, \(\cfrac{x^2+y^2}{x^2-y^2}=\cfrac{a^2+4a+4+a^2-4a+4}{a^2+4a+4-a^2+4a-4}\)
বা,\(\cfrac{x^2+y^2}{x^2-y^2}=\cfrac{(2a^2+4}{8a}\)
বা, \(\cfrac{x^2+y^2}{x^2-y^2}=\cfrac{a^2+4}{4a}\)
বা, \((x^2+y^2):(x^2-y^2)=a^2+4:4a\)
বা, \((x^2-y^2):(x^2+y^2)=4a:a^2+4\) (প্রমানিত)